(untitled) (Advances in Law, Pedagogy, and Multidisciplinary Humanities, 2025)
This study examined the impact of trauma on the academic adjustment of in-school adolescents in Benue and Nasarawa States, Nigeria. Guided by three research questions and three hypotheses, the study employed an ex-post facto research design. The population comprised 124,698 students from 622 public secondary schools, with a sample of 399 students selected through a multi-stage sampling procedure. Data were collected using the Trauma and Psycho-Academic Adjustment Questionnaire (TPAAQ), developed by the researcher. The instrument’s content and face validity were established through expert review, while a pilot test conducted on 40 students confirmed its test-retest reliability, yielding a high overall Cronbach’s Alpha coefficient of 0.93. Data were analyzed using Mean Score and Standard Deviation for the research questions, while chi-square statistics were used to test the hypotheses at a 0.05 significance level. The findings revealed that trauma significantly impacted class attendance, class participation, and concentration. Based on these findings, the study concluded that trauma adversely affected the academic adjustment of in-school adolescents in Benue and Nasarawa States. Consequently, it was recommended that the Ministries of Education in both states provide regular training for teachers on trauma-sensitive instructional strategies to enhance class participation and engagement among affected students.